Transferrin-modified cancer cell member coating hypocrellin B-derived nanomaterials for enhanced photodynamic therapy efficacy in hepatocellular carcinoma - Zhiqiang Zhang; Xianghui Li; Kai Zhao; Zhenhuan Guo; Yonglu Liu; Dai Zeng; Xueting Ban; Li Zhao; Xia Ma; Shizhong Zheng (Elsevier, 2021)
Hepatocellular carcinoma (HCC) has been reported to be the third common malignant tumor because of the high rate of mortality. Photosensitizers (PSs) based on the natural products have been widely used in clinical antitumor research contributed to their excellent biological activity. To increase the PSs' safety and efficacy of HCC, the tumor cell membrane coating drug nanocrystals featured with homologous immune escape and targeting ability and low toxicity are in high demand. In this study, we reported a targeting drug delivery system based on a modified cell membrane coating technique and drug nanocrystals. HepG2 cell membrane was modified with targeting receptor through a biochemical reaction including Maleimide reaction. Modified with the HepG2-targeting protein transferrin, the resulting TF-CCCM-HB NPs exhibited long-term stability, excellent biocompatibility, high drug loading, and low toxicity. Compared with HB NPs, TF-CCCM-HB NPs showed both excellent targeting and therapeutic efficacy in BALB/c nude mouse bearing with HepG2 tumors. Therefore, TF-CCCM, a biomimetic drug delivery platform, can be readily generalized to the delivery of various drugs and provide a sound strategy for the treatment of other cancers via changes in the corresponding homotypic cancer cell membrane.